The Drosophila GAGA transcription factor is associated with specific regions of heterochromatin throughout the cell cycle. - Raff, J W (1994)
In virtually all eukaryotes the centromeric regions of chromosomes are composed of heterochromatin, a specialized form of chromatin that is rich in repetitive DNA sequences and is transcriptionally relatively silent. The Drosophila GAGA transcription factor binds to GA/CT-rich sequences in many Drosophila promoters, where it activates transcription, apparently by locally altering chromatin structure and allowing other transcription factors access to the DNA. Here we report the paradoxical finding that GAGA factor is associated with specific regions of heterochromatin at all stages of the cell cycle. A subset of the highly repetitive DNA sequences that make up the bulk of heterochromatin in D. melanogaster are GA/CT-rich and we find a striking correlation between the distribution of GAGA factor and this class of repeat. We propose that GAGA factor binds directly to these repeats and may thereby play a role in modifying heterochromatin structure in these regions. Our observations demonstrate for the first time that a transcriptional regulator can associate with specific DNA sequences in a fully condensed mitotic chromosome. This may help explain how the distinctive character of a committed or differentiated cell can be maintained during cell proliferation.